The Influence of Social Media on the Realization of Christian Faith on The Environment of Saint Bernardus Pati - Milo Wardana; Hartutik Hartutik; Anselmus Joko Prayitno (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
The rapid development of Artificial Intelligence (AI) technology presents significant opportunities for transforming educational practices, such as personalization, rapid formative feedback, and administrative efficiency. However, AI adoption in schools also brings challenges related to values, particularly the potential erosion of students' positive character traits. These challenges include dependency on automated tools, tendencies toward plagiarism, weakening of moral obligations regarding academic honesty, and a decline in critical thinking skills concerning AI-generated content. This article aims to conduct a conceptual study and literature review of policies to: (a) map the relationship between AI adoption and student character issues; (b) identify the factors contributing to the character crisis in AI utilization; and (c) propose pedagogical intervention strategies, school policies, and research agendas to address these challenges. Key recommendations include integrating AI literacy and digital ethics into the curriculum, strengthening teacher capacity through practical training, designing policies that ensure human control over the learning process, and fostering collaboration between policymakers, educators, and technology developers. This collaborative effort will ensure that AI serves to enhance, rather than replace, the development of students' character.